Genetic transformation of cork oak (Quercus suber L.) for herbicide resistance. - Alvarez, Rubén; Alvarez, José M.; Humara, Jaime M.; Revilla, Angeles; Ordás, Ricardo J. (Biotechnology letters, 2009)
The bar gene was introduced into the cork oak genome. Cork oak embryogenic masses were transformed using the Agrobacterium strain AGL1 which carried the plasmid pBINUbiBar. This vector harbours the genes, nptII and bar, the latter under control of the maize ubiquitin promoter. The transgenic embryogenic lines were cryopreserved. Varying activities of phosphinothricin acetyl transferase were detected among the lines, which carried 1-4 copies of the insert. Molecular and biochemical assays confirmed the stability and expression of the transgenes 3 months after thawing the cultures. These results demonstrate genetic engineering of herbicide tolerance in Quercus spp.
The following values have no corresponding Zotero field: accession-num: 19543858
Keywords: Acetyltransferases; Acetyltransferases: genetics; Acetyltransferases: metabolism; Gene Dosage; Genomic Instability; Herbicide Resistance; Herbicides; Herbicides: toxicity; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plants, Genetically Modified; Plants, Genetically Modified: drug effects; Plants, Genetically Modified: genetics; Plants, Genetically Modified: physiology; Plasmids; Promoter Regions, Genetic; Quercus; Quercus: drug effects; Quercus: genetics; Quercus: physiology; Rhizobium; Rhizobium: genetics; Transformation, Genetic; Zea mays; Zea mays: genetics

Genetic transformation of cork oak (Quercus suber L.) for herbicide resistance. - Alvarez, Rubén; Alvarez, José M; Humara, Jaime M; Revilla, Angeles; Ordás, Ricardo J (Biotechnology letters, 2009)
The bar gene was introduced into the cork oak genome. Cork oak embryogenic masses were transformed using the Agrobacterium strain AGL1 which carried the plasmid pBINUbiBar. This vector harbours the genes, nptII and bar, the latter under control of the maize ubiquitin promoter. The transgenic embryogenic lines were cryopreserved. Varying activities of phosphinothricin acetyl transferase were detected among the lines, which carried 1-4 copies of the insert. Molecular and biochemical assays confirmed the stability and expression of the transgenes 3 months after thawing the cultures. These results demonstrate genetic engineering of herbicide tolerance in Quercus spp.
Keywords: Acetyltransferases; Acetyltransferases: genetics; Acetyltransferases: metabolism; Gene Dosage; Genomic Instability; Herbicide Resistance; Herbicides; Herbicides: toxicity; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plants, Genetically Modified; Plants, Genetically Modified: drug effects; Plants, Genetically Modified: genetics; Plants, Genetically Modified: physiology; Plasmids; Promoter Regions, Genetic; Quercus; Quercus: drug effects; Quercus: genetics; Quercus: physiology; Rhizobium; Rhizobium: genetics; Transformation, Genetic; Zea mays; Zea mays: genetics

Cork Oak Trees (Quercus suber L.). - Alvarez, Rubén; Toribio, Mariano; Cortizo, Millán; Ordás Fernández, Ricardo-Javier (Methods in molecular biology (Clifton, N.J.), 2006)
A transformation system for selected mature Quercus suber L. trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses are inoculated with AGL1 strain harbouring the plasmid pBINUbiGUSint, which carries the nptII and uidA genes. Evidence of stable transgene integration is obtained by polymerase chain reaction for nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos are germinated and successfully transferred to soil.
The following values have no corresponding Zotero field: periodical: Methods in molecular biology (Clifton, N.J.) accession-num: 17033056 electronic-resource-num: 10.1385/1-59745-131-2:113
Keywords: AGL1; Agrobacterium tumefaciens; Cork oak; Fagaceae; kanamycin resistance; pBINUbiGUSint; Quercus suber; Somatic embryogenesis; Tree genetic transformation; β-glucuronidase

Cork Oak Trees (Quercus suber L.). - Alvarez, Rubén; Toribio, Mariano; Cortizo, Millán; Ordás Fernández, Ricardo-Javier (Methods in molecular biology (Clifton, N.J.), 2006)
A transformation system for selected mature Quercus suber L. trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses are inoculated with AGL1 strain harbouring the plasmid pBINUbiGUSint, which carries the nptII and uidA genes. Evidence of stable transgene integration is obtained by polymerase chain reaction for nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos are germinated and successfully transferred to soil.
Keywords: AGL1; Agrobacterium tumefaciens; Cork oak; Fagaceae; kanamycin resistance; pBINUbiGUSint; Quercus suber; Somatic embryogenesis; Tree genetic transformation; β-glucuronidase